"Arroio Cadena: cartão postal de Santa Maria?": possibilidades e desafios em uma reorientação curricular na perspectiva da abordagem temática - Centa, Fernanda Gall (2015)
Curricular reorientation based on the Thematic Approach Freirean (TAF) articulated approach to Science, Technology and Society (STS) are possibilities, so that the linear curriculum, preparatory and fragmented schools is questioned and, for that to happen, it is essential to invest in the formation of educators. Thus, the research problem of this research is: What are the possibilities and challenges faced by educators Sciences (Biology, Physics and Chemistry), a public school in Santa Maria, to use the thematic approach in their classes, especially in structuring and implementing the theme "Arroio Cadena: Santa Postcard Maria? "?. In terms of research problem detailing, three objectives were assumed: Discuss how it came to Theme Generator to be developed from the study of Reality (SR); Develop a training collective and interdisciplinary process with educators, aimed at construction / reconstruction of the curriculum through the use of articulated TAF to focus STS; Investigate the possibilities and challenges encountered in the training process and in the development and implementation of educational design / learning. The survey was implemented in the State Preparatory High School Don Antonio Reis, in the city of Santa Maria / RS, during the year 2014. The theoretical reference used in the research is based on the TAF, following the steps of the Three Pedagogical Moments (3PM) as structuring the curriculum, assumptions of the educator Paulo Freire and ideals of focus STS and Latin American Thought in Science Technology and Society (LATSTS). The research was developed in different phases and in the first, It is made explicit the process for obtaining generator theme, from SR, and in the second, the formation process aiming at Thematic Approach (TA). With qualitative approach, the instruments used in the first phase were: document analysis of the school's pedagogical project; research in local newspapers; informal conversations with: Brazilian Institute of Geography and Statistics (BIGS), health post, prefecture, city planning institute and military brigade; interview with students, teachers, directive team and local community. In the second phase, the instruments used were: questionnaire on the first meeting of the formative process, daily researcher, recordings of the encounters of the formative process, teaching projects / elaborate learning, daily educators, interviews with educators and students. As a synthesis of research results initially is discussed as the generator theme emerged: Arroio Cadena: Postcard of Santa Maria? . Just after are discussed two emerging categories of analysis of the whole process using the Text Analysis Discourse (DTA) as methodology: Possibilities of an curricular reorientation the perspective of TA and Challenges of a curricular reorientation the perspective of TA In possibilities, are characteristics such as: interdisciplinary work and the extension of the collective work in school (school and local community), the contributions of the formative process in professional walk of educators, the shift in attitude and dialogue constructed between educator-students and awakening to a culture of participation. In the category of challenges, emerging problems related to the lack of time for interdisciplinary planning, the resistance of students in work developed and yet, the conceptual approach rooted in the concepts and practices.